The Impact of COVID-19 Pandemic on the Education System in Developing Countries - Willies, David (African Journal of Education and Practice, 2023)
Purpose: The purpose of this study is to investigate the impact of COVID-19 on the education systems in developing countries. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings of the study revealed the existence of a contextual and methodological gap relating to the impact of COVID-19 on the education systems in developing countries. Preliminary empirical review found that in the world, most schools, colleges, and universities are closed to control the spread of the COVID-19. Unique Contribution to Theory, Practice and Policy: The Disruption theory, Social Learning theory and the Cognitive Load theory may be used to anchor future studies on the impact of COVID-19 on education systems in developing countries. The COVID-19 pandemic has made all the educational schools across the world to adopt teaching and learning online. So, governments should scale network infrastructure and internet connectivity across urban and rural areas. The countries should design a strategy to scale educational technology, establish zero-rating educational resources on the internet, and prepare digital teaching and learning resources.